From Theology to Social Action: How Islamic Community Organization Conceptualize Islamic Philanthropy - Ahmad Rezy Meidina; Syaibani Ihza Ibrahim; Imam Sibawaih; Yudhi Hadiamsyah (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
This article examines the concept of Islamic philanthropy from the perspective of Nahdlatul Ulama and Muhammadiyah, based on the shift in the meaning of philanthropy compared to the classical understanding. Experts emphasize that philanthropy is a fundamental element in Islamic teachings, as seen in its various forms such as zakat one of the five pillars of Islam as well as infaq, sadaqah, and waqf. Therefore, philanthropy has a strategic position in the lives of Muslims. Although the meaning of philanthropy in the context of modern society has changed, the substance of philanthropy as an act of giving and spreading benefits remains unchanged. Islam plays a central role in building civilization, both through the spread of religion, the dissemination of knowledge, and the development of educational and social welfare institutions. Mosques as centers of da'wah (proselytizing) are one tangible manifestation of philanthropy, as exemplified by the Prophet Muhammad who established mosques as a means of spreading Islam. Similarly, educational institutions that function as centers for the transmission of knowledge also grew out of the practice of philanthropy, and it was through these institutions that the intellectual development of Islam took place. This article aims to provide the public with an understanding of the changing meaning of Islamic philanthropy by examining the views of Nahdlatul Ulama and Muhammadiyah as primary data. The analysis was conducted using the theory of Islamic legal change and a normative approach, with the aim of revealing the values of truth in the practice of Islamic philanthropy in society so that they can continue to be actualized in the future.